ä½¿ç”¨å¤šåª’ä½“æ¸¸æˆæé«˜Al Habib Sholehåˆä¸ äºŒå¹´çº§å¦ç”Ÿçš„è¯æ±‡è®°å¿†åŠ› - Gedinal, Jemi; ., Ina; ., Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
æ‘˜è¦ï¼šè¯æ±‡æ˜¯è¯è¨€ä¸å¿ƒï¼Œåˆ™è¯æ±‡æ˜¯å¦ä¼šä¸€ä¸ªè¯è¨€çš„é‡è¦å› ç´ ã€‚æ²¡æœ‰è¯æ±‡ï¼Œ å¦ç”Ÿæ— æ³•å‘åˆ«äººè¡¨è¾¾è‡ªå·±çš„æƒ³æ³•ã€‚Al Habib Sholehå¦ç”Ÿçš„å¦ä¹ éš¾ç‚¹æ˜¯æŽŒæ¡è¯æ±‡èƒ½åŠ›ä½Žã€‚å½“è€å¸ˆä½¿ç”¨æ±‰è¯æé—®æ—¶ï¼Œä»–ä»¬å´ä¸€ç›´å®‰é™åœ°å¾®ç¬‘ã€‚å› æ¤ï¼Œç¬”è€…çš„ç ”ç©¶ç›®çš„æ˜¯äº†è§£ä½¿ç”¨å¤šåª’ä½“æ¸¸æˆæ•™å¦æ³•çš„æ•™å¦è¿‡ç¨‹ä¸Žäº†è§£ä½¿ç”¨å¤šå¦¹ä½“æ¸¸æˆ æ•™å¦æ³•ï¼Œæé«˜å¦ç”Ÿå¯¹è¯æ±‡è®°å¿†åŠ›å’Œç†è§£èƒ½åŠ›ã€‚ç¬”è€…é‡‡ç”¨è¯¾å ‚å®žè·µä¸Žæµ‹è¯•æ³•åœ¨Al Habib Sholehåˆä¸äºŒå¹´çº§ç ”ç©¶å¦ç”Ÿçš„Â  è¯æ±‡è®°å¿†èƒ½åŠ›ã€‚åœ¨è°ƒæŸ¥è¿‡ç¨‹ä¸ï¼Œç¬”è€…å‘çŽ°å¦ç”Ÿå¯¹è¯æ±‡è®°å¿†èƒ½åŠ›ä½Žï¼Œå¦ç”Ÿå¯¹å¦ä¹ æ±‰è¯çš„å…´è¶£ä¹Ÿä¸é«˜ã€‚é€šè¿‡ç¬”è€…çš„æ•™å¦å®žè·µä¹‹åŽï¼Œæ€»ç»“å‡ºåº”ç”¨å¤šåª’ä½“æ¸¸æˆæ•™è¯æ±‡èƒ½æé«˜å¦ç”Ÿçš„è¯æ±‡è®°å¿†èƒ½åŠ›ä¸Žå…´è¶£ï¼Œå¦å¤–å‘çŽ°å¦ç”Ÿå¯¹è¯æ±‡æ•™å¦éš¾ç‚¹ï¼Œå¹¶æå‡ºäº†ç›¸å…³å»ºè®®ã€‚ å…³é”®è¯ï¼šè¯æ±‡ï¼›å¤šåª’ä½“ï¼›æ¸¸æˆï¼›æ•™å¦æ³• Abstract : Vocabularies are the source of language, they are on of the factors to master an important language. If there is no vocabularies, the students can not express their opinion. The problem of students Al habib Sholeh is the less vocabularies master. When the teacher asked in mandarin, the students only kept silent and laughed. Therefore, the script aim of the writer is how the teaching uses game based on right multimedia and for increasing students memorization and studentsâ€™ understanding. Writer using action research and examination on research in Â Â Â Â Â Al Habib Sholeh Junior High School grade 2 students. During the investigate, the writer found that students ability in memorize vocabularies is still low, studentsâ€™ interest in learning Chinese language is not high either. After teaching methods, we can conclude that use game based on multimedia method can improved studentâ€™s ability in memorize Mandarinâ€™s vocabularies and studentâ€™s interest in learning Mandarin, found that students difficulties in studying Mandarinâ€™s vocabularies and provide solutions in question. Key words: Vocabularies; Multimedia; Game; Teaching Methods